Kallmann syndrome and ichthyosis: a case of contiguous gene deletion syndrome. (28th September 2017) - Berges-Raso, Irene; Giménez-Palop, Olga; Gabau, Elisabeth; Capel, Ismael; Caixàs, Assumpta; Rigla, Mercedes
Summary: Kallmann syndrome is a genetically heterogeneous form of hypogonadotropic hypogonadism caused by gonadotropin-releasing hormone deficiency and characterized by anosmia or hyposmia due to hypoplasia of the olfactory bulbs; osteoporosis and metabolic syndrome can develop due to longstanding untreated hypogonadism. Kallmann syndrome affects 1 in 10 000 men and 1 in 50 000 women. Defects in 17 genes, including KAL1, have been implicated. Kallmann syndrome can be associated with X-linked ichthyosis, a skin disorder characterized by early onset dark, dry, irregular scales affecting the limb and trunk, caused by a defect of the steroid sulfatase gene ( STS ). Both KAL1 and STS are located in the Xp22.3 region; therefore, deletions in this region cause a contiguous gene syndrome. We report the case of a 32-year-old man with ichthyosis referred for evaluation of excessive height (2.07 m) and weight (BMI: 29.6 kg/m 2 ), microgenitalia and absence of secondary sex characteristics. We diagnosed Kallmann syndrome with ichthyosis due to a deletion in Xp22.3, a rare phenomenon. Learning points: Kallmann syndrome is a genetically heterogeneous disease characterized by hypogonadotropic hypogonadism with anosmia or hyposmia associated with defects in the production or action of gonadotropin-releasing hormone (GnRH) and hypoplasia of the olfactory bulbs. Several genes have been implicated in Kallmann syndrome, including KAL1, located in the Xp22.3 region, which is responsible for X-linked Kallmann syndrome. KAL1 encodes the protein anosmin-1. X-linked ichthyosis is caused by deficiency of the steroid sulfatase enzyme, encoded by STS, which is also located in the Xp22.3 region. Deletions involving this region can affect both genes and result in contiguous gene syndromes. Phenotype can guide clinicians toward suspicion of a specific genetic mutation. KAL1 mutations are mostly related to microgenitalia, unilateral renal agenesis and synkinesia, although patients need not present all these abnormalities. Longstanding untreated hypogonadism is associated with poor sexual health, osteoporosis and metabolic syndrome with the concomitant risk of developing type 2 diabetes mellitus and obesity. Treatment aims to promote the development of secondary sex characteristics, build and sustain normal bone and muscle mass and restore fertility. Treatment can also help minimize some psychological consequences. Treatments available for patients with congenital GnRH deficiency such as Kallmann syndrome include gonadal steroid hormones, human gonadotropins and GnRH. The choice of therapy depends on the goal or goals.